Americana : collection FRAC Nord-Pas de Calais - FRAC Nord Pas de Calais Dunkerque (Dunkerque : Nord-Pas de Calais, 2012)
Artists: Andy Warhol, Joan Wallace, Hedi Slimane, Meredyth Sparks, Mika Tajima, Taryn Simon, Collier Schorr, Raymond Pettibon, Laurie Parsons, and others.
Text in French and English.
Catalogue of an exhibition held at 2012.
boek